Examination of youth tobacco cessation needs, demand and services within the City of Greater Sudbury - Groulx, David R. (My University, 2008)
Tobacco use contributes to a significant amount of morbidity and mortality. Youth are interested in quitting smoking yet most often do not choose assisted cessation approaches which have been shown effective in the literature (CDC, 2006). Youth within the City of Greater Sudbury (CGS) have indicated a desire to quit smoking however anecdotal evidence has pointed to the lack of services in the area (Groulx, 2005; Sudbury & District Health Unit [SDHU], 2004a). To better understand local interest and demand for cessation services, analysis of a subset of data from the School Health Action, Planning and Evaluation System (SHAPES) Ontario (tobacco module) survey was completed. Data were derived from one secondary school in the CGS yielding 589 completed questionnaires. Analysis included frequencies, cross tabulations, and logistic regressions and focused on identification of local youths preferred cessation methods, factors most likely to impact youth success in smoking cessation, and factors influencing the students' preference to use assisted tobacco cessation methods/aids. Similar to previous studies which analyzed the provincial SHAPES dataset, most youth preferred to quit on their own. However, unlike previous literature, interest in, and factors contributing to interest in some assisted cessation methods was demonstrated. Analysis into the forces impacting the demand and provision of cessation services at the local level was also conducted. Despite the great capacity at the local level, environmental factors and provincial forces impacting the demand for cessation are evident as is the lack of youth specific cessation services. Recommendations for public health are proposed and are aimed at increasing demand for, and provision of evidence based cessation support for youth.
Keywords: Youth Tobacco use Ontario Sudbury; Teenagers Tobacco use Ontario Sudbury; Cigarette smokers Services for Ontario Sudbury